Pengaruh Strategi Belajar terhadap Hasil Belajar Siswa SMK di Indonesia: Studi Meta Analisis - Ramadhani, Restu Kurnia; Iskandar, Ranu; Naryanto, Rizqi Fitri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The purpose of this study was to evaluate the effect of learning strategies on the learning outcomes of vocational high school students in Indonesia. This study used a meta-analysis approach. Data were collected from Google Scholar and Semantic Scholar in February 2025. Keywords used Indonesian with a combination of "learning strategies", "field of expertise" and "learning outcomes of vocational high school students". The data entered were effect size, and standard error to produce a forest plot in which there were interval values ​​for each study and conclusion. A total of 15 articles met the criteria for analysis. The results showed that the effect size was 0.576, there was a significant influence between learning strategies and learning outcomes. The results of the meta-analysis showed a cumulative effect size of 0.576, indicating a moderate positive effect of learning strategies on vocational high school students' learning outcomes. However, the results of the subgroup analysis showed that the Inquiry Learning strategy (effect size = -0.959, 95% CI [-3.248, 1.331], p> 0.05) and Think-Pair-Share (effect size = -0.886, 95% CI [-3.188, 1.416], p> 0.05) had not shown a statistically significant effect because the confidence interval included the value of zero. Likewise, the areas of expertise of Manufacturing and Engineering Technology and Information Technology showed results that were not yet statistically significant. These findings provide an illustration that although learning strategies have the potential to improve learning outcomes in general, the specific effectiveness of certain strategies requires further study with a wider range of data.